Electrode material for aluminum electrolytic capacitor and its manufacturing method
Patent Information
- Application Number
- JP2021018442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-02-08
AI Technical Summary
【0016】 本発明のアルミニウム電解コンデンサ用電極材は、コンデンサに要求される静電容量を示すことができ、且つ、折曲強度に優れる。
Smart Images

Figure 0007635010000004 
Figure 0007635010000005 
Figure 0007635010000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode material for an aluminum electrolytic capacitor and a method for producing the same. [Background technology]
[0002] Aluminum electrolytic capacitors are widely used in the energy sector because they are inexpensive and can provide high capacity. Aluminum foil is generally used as the electrode material for aluminum electrolytic capacitors.
[0003] The surface area of aluminum foil can be increased by etching it to form etching pits. Then, anodizing the surface of the aluminum foil forms an oxide film, which functions as a dielectric. Therefore, by etching the aluminum foil and forming an anodized film on the surface at various voltages according to the voltage to be used, it is possible to manufacture various aluminum anode electrode foils for electrolytic capacitors that are suited to the intended use.
[0004] The etching pits formed by the etching process are processed into a shape corresponding to the anodizing voltage. Specifically, for medium-high voltage capacitor applications, it is necessary to form a thick oxide film. For this reason, in order to prevent the etching pits from being filled with such a thick oxide film, in aluminum foil for medium-high voltage anodes, direct current etching is mainly performed to form tunnel-type etching pits with a width corresponding to the voltage. For low-voltage capacitor applications, fine etching pits are required, and spongy etching pits are mainly formed by alternating current etching. Similarly, the surface area of the cathode foil is also expanded by etching.
[0005] Patent Document 1 proposes an electrode material for aluminum electrolytic capacitors, which is characterized by being made of at least one sintered body of aluminum and an aluminum alloy. The electrode material has a larger surface area than conventional aluminum foils with etched pits, and the capacitance of a capacitor using the electrode material can be increased. Furthermore, it is disclosed that the use of aluminum powder with an average particle size of 1 to 80 μm results in an electrode material for aluminum electrolytic capacitors that is excellent in terms of withstand voltage and capacitance.
[0006] However, the electrode material for aluminum electrolytic capacitors disclosed in Patent Document 1 also has problems with strength, and is particularly prone to breakage during anodizing. As described above, the electrode material for aluminum electrolytic capacitors disclosed in Patent Document 1 is obtained by sintering a film made of a paste composition containing aluminum powder and / or aluminum alloy powder. Here, when manufacturing an aluminum electrolytic capacitor, the aluminum anode foil (material) is often wound with a very small diameter together with the separator and cathode foil (material). In order to withstand this winding, the electrode material for aluminum electrolytic capacitors that constitutes the aluminum anode foil is required to have high bending strength.
[0007] It is possible to increase the bending strength of the electrode material for aluminum electrolytic capacitors by increasing the particle size of the aluminum powder and / or aluminum alloy powder used in the manufacture of the electrode material for aluminum electrolytic capacitors. However, in this case, the surface area of the electrode material for aluminum electrolytic capacitors is reduced, and therefore, when the electrode material for aluminum electrolytic capacitors is used to manufacture an aluminum electrolytic capacitor, the capacitance of the capacitor is reduced. Conversely, if the particle size of the aluminum powder and / or aluminum alloy powder is reduced to increase the capacitance of the electrode material for aluminum electrolytic capacitors, the bending strength of the electrode material for aluminum electrolytic capacitors becomes insufficient.
[0008] Furthermore, Patent Document 2 discloses that when forming an electrode material for an aluminum electrolytic capacitor, a sintered body is embossed to adjust the surface roughness of the sintered body to a predetermined range to make the electrode material for an aluminum electrolytic capacitor less susceptible to fracture during the anodizing process.
[0009] However, even the method disclosed in Patent Document 2 has room for improvement in terms of the capacitance and manufacturing cost of the capacitor. The manufacturing method disclosed in Patent Document 2 requires an embossing process, which has the problem of increasing manufacturing costs. Furthermore, there is a problem that the capacitance tends to decrease if the embossing is too deep.
[0010] Patent Document 3 discloses that when forming an electrode material for an aluminum electrolytic capacitor, by manufacturing the electrode material for an aluminum electrolytic capacitor using an aluminum foil base material (aluminum foil as a base material) to which manganese (Mn) has been added, the electrode material becomes less likely to break during the anodizing treatment process.
[0011] However, when manufacturing a capacitor using an anodized electrode material, it is difficult to say that the manufacturing method disclosed in Patent Document 3 can sufficiently prevent damage to the electrode material and the anodized film during the winding process, and an electrode material with better bending strength is needed. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2008-98279 A [Patent Document 2] International Publication No. 2016 / 136804 [Patent Document 3] International Publication No. 2015 / 098644 Summary of the Invention [Problem to be solved by the invention]
[0013] An object of the present invention is to provide an electrode material for an aluminum electrolytic capacitor that is capable of exhibiting the capacitance required for a capacitor and has excellent bending strength, and a method for producing the same. [Means for solving the problem]
[0014] As a result of intensive research, the present inventors have determined that the total thickness of the sintered body is within a specific range, and the 10% particle diameter D 10 , 50% particle size D 50 , and 90% particle size D 90 The present inventors have found that by setting the content of the conductive material in the electrode material to a specific range, an electrode material excellent in bending strength and electrostatic capacitance can be produced, and have completed the present invention.
[0015] That is, the present invention relates to the following electrode material for aluminum electrolytic capacitors and a method for producing the same. 1. An electrode material for an aluminum electrolytic capacitor having an aluminum foil substrate or an aluminum alloy foil substrate, on at least one surface of which is a sintered body of at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder, (1) the total thickness of the sintered body is 50 to 900 μm; (2) 10% particle size D in the particle size distribution based on the number of powder particles in the sintered body 10 is 1.0 to 1.8 μm, (3) The 50% particle size D in the particle size distribution based on the number of powder particles in the sintered body 50 is 2.0 to 3.5 μm, (4) 90% particle size D in the particle size distribution based on the number of powder particles in the sintered body 90 is 3.8 to 6.0 μm. Electrode material for aluminum electrolytic capacitors. 2. An electrode material for an aluminum electrolytic capacitor according to item 1, wherein the number of powder particles having a particle diameter of 1 μm or less within any given area of 100 μm × 115 μm on the surface of the sintered body is 300 or less. 3. The electrode material for an aluminum electrolytic capacitor according to item 1 or 2, further comprising an anodized film on a surface of the sintered body. 4. (1) A first step of forming a coating of a paste composition containing at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder on at least one surface of an aluminum foil or an aluminum alloy foil; and (2) a second step of sintering the coating at a temperature of 560° C. or more and 660° C. or less; The powder has a 10% particle size D 10 is 1.0 to 1.8 μm, and the 50% particle diameter D 50 is 2.0 to 3.5 μm, and the 90% particle diameter D 90 is 3.8 to 6.0 μm, A method for producing an electrode material for an aluminum electrolytic capacitor, comprising the steps of: 5. The manufacturing method according to item 4, further comprising an anodizing treatment step after the second step. Effect of the Invention
[0016] The electrode material for an aluminum electrolytic capacitor of the present invention can exhibit the capacitance required for a capacitor and is excellent in bending strength. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a graph showing the particle size distribution based on the number of particles of the powders used in Example 1 and Comparative Example 5. [Diagram 2] FIG. 2 is a graph showing the volume-based particle size distribution of the powders used in Example 1 and Comparative Example 5. [Diagram 3] 1 is an image of the surface of the sintered body of the electrode material produced in Example 1, photographed with a SEM (scanning electron microscope) and processed with image analysis software. [Figure 4] 1 is an image of the surface of the sintered body of the electrode material produced in Example 2, photographed with a SEM (scanning electron microscope) and processed with image analysis software. [Diagram 5]1 is an image of the surface of the sintered body of the electrode material produced in Comparative Example 1, photographed with a SEM (scanning electron microscope) and processed with image analysis software. [Figure 6] 1 is an image of the surface of the sintered body of the electrode material produced in Comparative Example 5, photographed with a SEM (scanning electron microscope) and processed with image analysis software. [Figure 7] FIG. 1 is a diagram for explaining a test method for a folding strength evaluation test. [Figure 8] 1 is an image taken with a SEM (scanning electron microscope) of the surface of a sintered electrode material produced according to Comparative Example 1 and after a bending strength evaluation test was performed. [Figure 9] 1 is an image taken with a SEM (scanning electron microscope) of the surface of a sintered electrode material produced according to Comparative Example 1 and after a bending strength evaluation test was performed. [Figure 10] 1 is an image taken with a SEM (scanning electron microscope) of the surface of a sintered electrode material produced according to Comparative Example 1 and after a bending strength evaluation test was performed. [Figure 11] 2 is an image of the surface of the sintered body of the electrode material produced in Example 1 taken with a SEM (scanning electron microscope). [Figure 12] 2 is an image of the surface of the sintered body of the electrode material produced in Example 1 taken with a SEM (scanning electron microscope). [Figure 13] 2 is an image of the surface of a sintered body of an electrode material produced in Comparative Example 1, taken with a SEM (scanning electron microscope). [Figure 14] 2 is an image of the surface of a sintered body of an electrode material produced in Comparative Example 1, taken with a SEM (scanning electron microscope). [Figure 15] 1 is an image of the surface of a sintered body of an electrode material produced in Comparative Example 4 taken with a SEM (scanning electron microscope). [Figure 16] 1 is an image of the surface of a sintered body of an electrode material produced in Comparative Example 4 taken with a SEM (scanning electron microscope). [Figure 17] 1 is an image taken with a SEM (scanning electron microscope) of the surface of a sintered electrode material produced in Example 1 and after being folded twice in a folding strength evaluation test. [Figure 18]1 is an image taken with a SEM (scanning electron microscope) of the surface of a sintered electrode material produced according to Comparative Example 1 and after being folded twice in a folding strength evaluation test. [Figure 19] 1 is an image taken with a SEM (scanning electron microscope) of the surface of a sintered electrode material produced in Comparative Example 5 and after being folded twice in a folding strength evaluation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] 1. Electrode materials for aluminum electrolytic capacitors The electrode material for an aluminum electrolytic capacitor of the present invention is an electrode material for an aluminum electrolytic capacitor having a sintered body of at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder on at least one surface of an aluminum foil substrate or an aluminum alloy foil substrate, wherein (1) the total thickness of the sintered body is 50 to 900 μm, (2) the 10% particle diameter D 10 (3) the 50% particle diameter D in the particle diameter distribution based on the number of powder particles in the sintered body is 1.0 to 1.8 μm; 50 (4) the 90% particle diameter D in the particle diameter distribution based on the number of powder particles in the sintered body is 2.0 to 3.5 μm; 90 The electrode material for aluminum electrolytic capacitors has a thickness of 3.8 to 6.0 μm.
[0019] Generally, the particle size distribution of a powder is measured by, for example, a laser diffraction / scattering method to determine the volumetric average particle diameter D 50 However, the average particle diameter D 50 However, the distribution varies widely, and since measurements are made on a volume basis, the presence (number) of fine particles is difficult to detect. Powder with a particle size of 1 μm or less, which is difficult to detect in volume-based particle size distribution, can cause cracks and reduce the bending strength of electrode materials for aluminum electrolytic capacitors.
[0020] The electrode material for aluminum electrolytic capacitors of the present invention (hereinafter, also simply referred to as "electrode material") has the above-mentioned (2) to (4) configurations, and therefore contains less fine powder, suppresses the generation of secondary particles formed by aggregation of fine powder that can be the starting point of cracks, and, together with satisfying the above-mentioned (1), can improve bending strength. In addition, the electrode material of the present invention has the above-mentioned (2) to (4) configurations, and therefore the particle size of the powder falls within an appropriate range, and can exhibit high capacitance.
[0021] Fig. 1 is a diagram showing the particle size distribution based on the number of particles of the powders used in Example 1 of the present invention and Comparative Example 5. Fig. 1 shows that the particle size distribution of the powder used in Example 1 has almost no peak in the small particle size region (2 µm or less), indicating that there are few particles with small particle sizes. In contrast, the particle size distribution of the powder used in Comparative Example 5 has a large peak at 0.81 µm, indicating that there are many particles with small particle sizes.
[0022] Fig. 2 is a diagram showing the volumetric particle size distribution of the powders used in Example 1 of the present invention and Comparative Example 5. In Fig. 2, the powders used in Example 1 and Comparative Example 5 do not show a peak in the small particle size region (2 µm or less), and the presence of particles with small particle sizes is unclear in the volumetric particle size distribution.
[0023] The electrode material of the present invention will be described in detail below.
[0024] (Sintered body) The electrode material of the present invention has, on at least one surface of an aluminum foil substrate, a sintered body of at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder.
[0025] The sintered body may be formed on at least one side of the aluminum foil substrate, and may be formed on both sides. It is preferable that the sintered body is formed on both sides in order to further improve the capacitance of the electrode material.
[0026] The sintered body is preferably a porous sintered body having a three-dimensional network structure formed by sintering and bonding the powders together while maintaining voids. The structure increases the surface area of the sintered body, making it possible to obtain an electrode material that can be used to manufacture an aluminum electrolytic capacitor (hereinafter, simply referred to as a "capacitor") that exhibits high capacitance.
[0027] The aluminum content of the aluminum powder is preferably 99.80 mass % or more, more preferably 99.85 mass % or more, and even more preferably 99.99 mass % or more.
[0028] The aluminum alloy powder may contain one or more elements selected from silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), zirconium (Zr), etc. The content of these elements in the aluminum alloy is preferably 100 mass ppm or less, more preferably 50 mass ppm or less. When the content of the above elements in the aluminum alloy powder is within the above range, the capacitance of the electrode material for aluminum electrolytic capacitors is further improved.
[0029] The above powders may be used alone or in combination of two or more.
[0030] 50% particle diameter D in the number-based particle size distribution of powder in the sintered body 50 (Hereinafter, "number-based particle diameter D 50 ", "D 50 " is also indicated. ) is 2.0 μm or more and 3.5 μm or less. Number-based particle diameter D 50 If the particle diameter D of the powder in the sintered body is less than 2.0 μm or exceeds 3.5 μm, the capacitance of the electrode material is insufficient. 50 is preferably 2.2 μm or more and 3.3 μm or less, more preferably 2.3 μm or more and 3.0 μm or less, and even more preferably 2.4 μm or more and 2.8 μm or less.
[0031] In this specification, the particle diameter D of the powder in the sintered body based on the number of particles 50 can be measured by observing the cross section of the sintered body with a scanning electron microscope. Specifically, when the above powder is sintered to form a sintered body, some of the particulate powder in the sintered body is sintered and the powder particles are bonded together. In the cross section of the sintered body, the maximum diameter (longest diameter) of each powder in the bonded state is taken as the particle diameter of that powder, and the particle diameter and number of all particles in a certain area in the cross section image are obtained. All the particles thus obtained are arranged in order of smallest particle diameter, and the particle diameter of the particle that makes up 50% of the number of particles is taken as the number-based particle diameter D of the powder in the sintered body. 50 The particle sizes that make up 10% and 90% of the total number of particles are defined as the particle sizes D based on the number of particles in the sintered body as shown below. 10 , D 90 Let us assume that.
[0032] Number-based particle diameter D of the powder in the sintered body 10 is 1.0 μm or more and 1.8 μm or less. 10 If the particle diameter D is less than 1.0 μm, the amount of fine powder in the powder in the sintered body increases, the number of secondary particles that may cause cracks increases, and the bending strength of the electrode material decreases. 10 If the particle diameter D exceeds 1.8 μm, the yield in the manufacturing process of the aluminum powder material will decrease and the cost will increase. 10 From the viewpoints of bending strength and cost, the thickness is preferably 1.3 μm or more and 1.7 μm or less, and more preferably 1.4 μm or more and 1.5 μm or less.
[0033] Number-based particle diameter D of the powder in the sintered body 90 is 3.8μm or more and 6.0μm or less. 90 If the particle size is less than 3.8 μm, the yield in the manufacturing process of the aluminum powder material will decrease and the cost will increase. 90 If the particle diameter D exceeds 6.0 μm, the surface area of the sintered body is insufficient, and the capacitance is insufficient when used as an electrode material for a capacitor. 90In terms of capacitance when used as an electrode material for a capacitor, the thickness is preferably 3.9 μm or more and 5.0 μm or less, and more preferably 3.9 μm or more and 4.5 μm or less.
[0034] The particle diameter D of the powder in the sintered body measured by the above-mentioned measuring method is based on the number of particles. 10 , D 50 , D 90 is the particle size D of the powder before sintering based on the number of particles 10 , D 50 , D 90 Since the particle diameter D of the powder before sintering hardly changes and is almost the same, 10 , D 50 , D 90 The measured value is the particle diameter D of the powder in the sintered body based on the number of particles. 10 , D 50 , D 90 In this specification, the particle diameter D of the powder before sintering based on the number of particles 10 , D 50 , D 90 The particle size distribution was measured on a number basis using a Microtrac MT3300EXII (manufactured by Nikkiso Co., Ltd.) by wet measurement using the laser diffraction / scattering method. 10 Value, D 50 Value and D 90 The value can be measured by calculating the value.
[0035] D in the above particle size distribution based on number 10 , D 50、 D 90 The powder having the above range can be obtained by classifying the atomized aluminum powder by a method such as vortex classification or sieve classification. 10 A classifier in which D is within the above range 50 A classifier in which D is within the above range, and 90 (2) classifying the atomized aluminum powder by a method such as vortex classification or sieve classification to obtain a powder having a diameter of 100 mm or less, and then classifying the atomized aluminum powder. 10 Aluminum powder having the above range, D 50 The above range of aluminum powder 、 D90 The aluminum powders each having the above-mentioned average particle diameter are prepared and then mixed together.
[0036] The total thickness of the sintered body is 50 μm or more and 900 μm. If the total thickness of the sintered body is less than 50 μm, the capacitance of the electrode material is insufficient. It is difficult to form a sintered body having a total thickness of more than 900 μm. The total thickness of the sintered body is preferably 70 μm or more, more preferably 100 μm or more. The total thickness of the sintered body is preferably 875 μm or less, more preferably 860 μm or less, even more preferably 500 μm or less, and particularly preferably 300 μm or less. In this specification, the total thickness of the sintered body is the total thickness of the thicknesses of the sintered bodies formed on each side when the electrode material of the present invention has a sintered body on both sides of the aluminum foil base material. When the electrode material of the present invention has a sintered body on only one side of the aluminum foil base material, the thickness of the sintered body on one side is the total thickness.
[0037] The number of powder particles having a particle diameter of 1 μm or less in any region of 100 μm×115 μm on the surface of the sintered body is preferably 300 or less, more preferably 250 or less, even more preferably 200 or less, and particularly preferably 180 or less. By setting the upper limit of the number of powder particles having a particle diameter of 1 μm or less within the above range, the amount of fine powder in the powder in the sintered body is reduced, and the increase in the number of secondary particles that cause cracks is suppressed, and the bending strength of the electrode material of the present invention is further improved, so that breakage during the anodizing line or winding process when the electrode material is used as a capacitor electrode can be further suppressed. In addition, the lower limit of the number of powder particles having a particle diameter of 1 μm or less is preferably as low as possible, but it may be 0, 50 or more, or 100 or more.
[0038] In this specification, the number of powder particles having a particle diameter of 1 μm or less in an arbitrary region of 100 μm × 115 μm on the surface of the sintered body can be measured by analyzing an image of the surface of the sintered body taken with a scanning electron microscope, processing the image with image analysis software, and counting the number of powder particles having a particle diameter of 1 μm or less in an arbitrary region of 100 μm × 115 μm on the surface of the sintered body. This will be explained in more detail below.
[0039] The photographing with the scanning electron microscope is performed using a JEOL scanning electron microscope (product number: JSM-5510) under the conditions of secondary electron image, photographing magnification of 1500 times, acceleration voltage of 15 kV, spot diameter of 15, and working distance of 20 mm.
[0040] Next, the number of powder particles with a particle diameter of 1 μm or less on the surface of the sintered layer is calculated using image analysis software WinROOF2015 manufactured by Mitani Shoji Co., Ltd. Specifically, the image taken with the scanning electron microscope is imported into the software as a JPEG image, and a "monochrome conversion" process is performed, followed by a "binarization" process. After that, within any 100 μm x 115 μm range in the image, the circle equivalent diameter of each powder particle is taken as the particle diameter of that powder, and the number of powder particles with a particle diameter of 1 μm or less is counted to measure.
[0041] (Aluminum foil base material, aluminum alloy foil base material) The electrode material of the present invention has an aluminum foil substrate or an aluminum alloy foil substrate (hereinafter, also referred to as "substrate").
[0042] As the aluminum foil forming the aluminum foil substrate, it is preferable to use an aluminum foil made of pure aluminum.
[0043] The aluminum content of the aluminum foil made of pure aluminum is preferably 99.80% by mass or more, more preferably 99.85% by mass or more, and even more preferably 99.99% by mass or more.
[0044] The aluminum alloy used for the aluminum alloy foil forming the aluminum alloy foil substrate may be an aluminum alloy in which at least one metal element selected from the group consisting of silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni) and boron (B) is added to aluminum within a necessary range, or may be an aluminum alloy containing the above elements as unavoidable impurities. The content of these elements in the aluminum alloy is preferably 100 mass ppm or less, more preferably 50 mass ppm or less. By the content of the above elements in the aluminum alloy being within the above range, the capacitance of the electrode material for aluminum electrolytic capacitors is further improved.
[0045] The thickness of the substrate is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more from the viewpoint of further improving the strength of the electrode material, and the thickness of the aluminum foil substrate is preferably 80 μm or less, more preferably 60 μm or less, and even more preferably 40 μm or less from the viewpoint of further improving the capacity per volume when used as an electrode material for a capacitor.
[0046] (anodic oxide film) The electrode material of the present invention may further have an anodized film on the surface of the sintered body. By having an anodized film on the surface of the sintered body, the anodized film functions as a dielectric, and the electrode material of the present invention can be usefully used as an electrode material for an aluminum electrolytic capacitor.
[0047] The anodic oxide film can be produced by anodizing the surface of the sintered body. The anodic oxide film functions as a dielectric film.
[0048] The thickness of the anodized film is preferably 0.2 to 1.1 μm, and more preferably 0.3 to 1.05 μm.
[0049] The anodized film has a withstand voltage of preferably 250 to 800 V, and more preferably 300 to 800 V. The withstand voltage of the anodized film can be measured by a measurement method in accordance with the Electronic Industries Association of Japan standard RC-2364A.
[0050] 2. Manufacturing method of electrode material for aluminum electrolytic capacitors The method for producing an electrode material for an aluminum electrolytic capacitor of the present invention comprises the steps of: (1) A first step of forming a coating of a paste composition containing at least one powder selected from the group consisting of aluminum powder and aluminum alloy powder on at least one surface of an aluminum foil substrate or an aluminum alloy foil substrate; and (2) a second step of sintering the coating at a temperature of 560° C. or more and 660° C. or less; The powder has a 10% particle diameter D 10 is 1.0 to 1.8 μm, and the 50% particle diameter D 50 is 2.0 to 3.5 μm, and the 90% particle diameter D 90 This is a manufacturing method in which the thickness is 3.8 to 6.0 μm. The details will be explained below.
[0051] (1st step) The first step is (1) forming a coating of a paste composition containing at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder on at least one surface of an aluminum foil substrate or an aluminum alloy foil substrate (hereinafter, also referred to as "substrate").
[0052] As the raw aluminum powder, for example, aluminum powder with an aluminum purity of 99.80 mass% or more is preferable, aluminum powder with an aluminum purity of 99.85 mass% or more is more preferable, and aluminum powder with an aluminum purity of 99.99 mass% or more is even more preferable. In addition, as the raw aluminum alloy powder, for example, an alloy containing one or more of elements such as silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), chromium (Cr), zinc (Zn), titanium (Ti), vanadium (V), gallium (Ga), nickel (Ni), boron (B), and zirconium (Zr) is preferable. The content of these elements in the aluminum alloy is preferably 100 mass ppm or less, particularly 50 mass ppm or less.
[0053] The above powders may be used alone or in combination of two or more.
[0054] 50% particle size D in the powder particle size distribution based on number 50 is 2.0 μm or more and 3.5 μm or less. 50 If the particle diameter D of the powder is less than 2.0 μm or exceeds 3.5 μm, the capacitance of the electrode material produced is insufficient. 50 is preferably 2.2 μm or more and 3.3 μm or less, more preferably 2.3 μm or more and 3.0 μm or less, and even more preferably 2.4 μm or more and 2.8 μm or less.
[0055] Number-based particle size of powder D 10 is 1.0 μm or more and 1.8 μm or less. 10 If the particle diameter D is less than 1.0 μm, the amount of fine powder in the powder increases, the number of secondary particles that may cause cracks increases, and the bending strength of the electrode material produced decreases. 10 If the particle diameter D exceeds 1.8 μm, the yield in the manufacturing process of the aluminum powder material will decrease and the cost will increase. 10 From the viewpoints of bending strength and cost, the thickness is preferably 1.3 μm or more and 1.7 μm or less, and more preferably 1.4 μm or more and 1.5 μm or less.
[0056] Number-based particle size of powder D 90 is 3.8μm or more and 6.0μm or less. 90 If the particle size is less than 3.8 μm, the yield in the manufacturing process of the aluminum powder material will decrease and the cost will increase. 90 If the particle diameter D exceeds 6.0 μm, the surface area of the sintered body is insufficient, and the capacitance is insufficient when used as an electrode material for a capacitor. 90 In terms of capacitance when used as an electrode material for a capacitor, the thickness is preferably 3.9 μm or more and 5.0 μm or less, and more preferably 3.9 μm or more and 4.5 μm or less.
[0057] The particle size D based on the number of powder particles 10 , D 50 , D 90 The particle size distribution was measured on a number basis using a Microtrac MT3300EXII (manufactured by Nikkiso Co., Ltd.) by wet measurement using the laser diffraction / scattering method. 10 Value, D 50 Value and D 90 The value can be measured by calculating the value.
[0058] D in the above particle size distribution based on number 10 , D 50、 D 90 The powder having the above range can be obtained by classifying the atomized aluminum powder by a method such as vortex classification or sieve classification. 10 A classifier in which D is within the above range 50 A classifier in which D is within the above range, and 90 (2) classifying the atomized aluminum powder by a method such as vortex classification or sieve classification to obtain a powder having a diameter of 100 mm or less, and then classifying the atomized aluminum powder. 10 Aluminum powder having the above range, D 50 The above range of aluminum powder 、 D 90The aluminum powders each having a molecular weight in the above range are prepared and then mixed together.
[0059] The shape of the aluminum powder and aluminum alloy powder is not particularly limited, and any shape such as spherical, irregular, scaly, fibrous, etc. can be suitably used, but for industrial production, a powder consisting of spherical particles is particularly preferred.
[0060] The paste composition may contain a resin binder. A wide variety of known resin binders can be used, including, for example, synthetic resins such as carboxy-modified polyolefin resins, vinyl acetate resins, vinyl chloride resins, vinyl chloride-vinyl acetate copolymer resins, vinyl alcohol resins, butyral resins, vinyl fluoride resins, acrylic resins, polyester resins, urethane resins, epoxy resins, urea resins, phenolic resins, acrylonitrile resins, cellulose resins, paraffin wax, and polyethylene wax, as well as natural resins or waxes such as wax, tar, glue, urushi, rosin, and beeswax. Depending on the molecular weight, type of resin, and the like, these resin binders include those that volatilize when heated and those that remain as residues together with the aluminum powder due to thermal decomposition, and can be used according to the desired electrical properties such as capacitance.
[0061] The content of the resin binder in the paste composition is preferably 0.5 to 10 mass% and more preferably 0.75 to 5 mass% in 100 mass% of the paste-like composition. By making the amount of the resin binder in the paste composition 0.5 mass% or more, the adhesive strength between the substrate and the unsintered laminate can be improved. On the other hand, by making the amount of the resin binder 10 mass% or less, degreasing is easily performed in the sintering step and the degreasing step, and defects caused by remaining resin binder can be suppressed.
[0062] In addition, the paste composition may contain a solvent, a sintering aid, a surfactant, etc., as necessary. Any of these may be known or commercially available. This allows the coating to be formed efficiently.
[0063] As the solvent, a wide variety of known solvents can be used, including, for example, water, toluene, alcohols, ketones, esters, and other organic solvents.
[0064] As the sintering aid, a wide variety of known sintering aids can be used, such as aluminum fluoride and potassium fluoride.
[0065] As the surfactant, a wide variety of known surfactants can be used, such as betaine, sulfobetaine, and alkylbetaine surfactants.
[0066] When the paste composition is applied to one or both sides of a substrate to form a coating of the paste composition, the total thickness of the coating is preferably 50 μm or more and 900 μm or less. The total thickness of the coating is preferably 70 μm or more, more preferably 100 μm or more. The total thickness of the coating is preferably 875 μm or less, more preferably 860 μm or less, even more preferably 500 μm or less, and particularly preferably 300 μm or less. In this specification, the total thickness of the coating is the total thickness of the coating formed on each side when the coating is formed on both sides of the substrate in the first step. When the coating is formed on only one side of the substrate in the first step, the thickness of the coating on one side is the total thickness.
[0067] The method for forming a coating on a substrate is not particularly limited, and the coating can be formed by applying a paste composition using a coating method such as die coating, gravure coating, direct coating, roller coating, brush coating, spraying, dipping, or the like, or by a known printing method such as silk screen printing.
[0068] If necessary, it is also preferable to dry the coating deposited on the substrate together with the substrate at a temperature within the range of 20 to 300° C. for 1 to 30 minutes.
[0069] (2nd process) The second step is (2) sintering the coating at a temperature of 560°C or higher and 660°C or lower.
[0070] The powder in the coating is sintered in the second step, forming a sintered body on the substrate. The sintering temperature is 560°C or higher and 660°C or lower. If the sintering temperature is lower than 560°C, the sintering does not proceed and the desired capacitance is not obtained. If the sintering temperature is higher than 660°C, the powder melts and sufficient capacitance is not obtained when used as an electrode material for an electrolytic capacitor. The sintering temperature is preferably 570°C or higher and lower than 650°C, more preferably 580°C or higher and lower than 620°C.
[0071] The sintering time is influenced by the sintering temperature, etc., but can usually be appropriately determined within a range of about 5 to 24 hours. The sintering atmosphere is not particularly limited, and may be, for example, a vacuum atmosphere, an inert gas atmosphere, an oxidizing gas atmosphere (air), a reducing atmosphere, etc., but a vacuum atmosphere or a reducing atmosphere is particularly preferable. The pressure condition may be normal pressure, reduced pressure, or increased pressure.
[0072] (Degreasing process) In the manufacturing method of the present invention, it is preferable to carry out a degreasing step prior to the second step in order to vaporize the resin binder in the film. The degreasing step can be, for example, a step of heating in an oxidizing gas atmosphere (air) at 200 to 500°C for 1 to 20 hours. By setting the lower limit of the heating temperature or the lower limit of the heating time within the above range, the resin binder in the film is more vaporized, and the resin binder can be prevented from remaining in the film. Furthermore, by setting the upper limit of the heating temperature or the upper limit of the heating time within the above range, excessive sintering of the aluminum powder in the film can be prevented, and the capacity when used as an electrode material for an electrolytic capacitor becomes even more sufficient.
[0073] (Anodizing process) The manufacturing method of the present invention may further include an anodizing treatment step after step 2. By including the anodizing treatment step, an anodized film is formed on the surface of the sintered body, and the anodized film functions as a dielectric, so that the electrode material can be usefully used as an electrode material for an aluminum electrolytic capacitor.
[0074] The anodizing conditions are not particularly limited, and generally, the electrode material that has been subjected to the first and second steps is anodized in an aqueous solution of boric acid or ammonium adipate at a concentration of 0.01 to 5 mol and a temperature of 30 to 100° C. at a current of 10 mA / cm. 2 More than 400mA / cm 2 The following current may be applied for 5 minutes or more. In a production line, the above-mentioned anodizing treatment is usually carried out while the electrode material is being fed by one or more rolls.
[0075] Moreover, the voltage in the above anodizing treatment step is preferably selected from the range of 250 to 800 V. It is preferable that the treatment voltage corresponds to the operating voltage of an aluminum electrolytic capacitor when used as an aluminum electrolytic capacitor electrode.
[0076] According to the method for producing an electrode material of the present invention, an excellent electrode material can be obtained without performing an etching process. Since the method does not include an etching step, treatment with hydrochloric acid or the like used in etching is not required, and the environmental and economic burdens are further reduced.
[0077] (Manufacturing method of electrolytic capacitor) An electrolytic capacitor can be manufactured using the electrode material of the present invention. Examples of methods for manufacturing the electrolytic capacitor include the following methods. That is, the electrode material of the present invention is used as an anode foil, and the anode foil and a cathode foil are laminated with a separator interposed therebetween and wound to form a capacitor element. The capacitor element is impregnated with an electrolytic solution, and the capacitor element containing the electrolytic solution is housed in an exterior case, and the exterior case is sealed with a sealer.
[0078] Although the embodiment of the present invention has been described above, the present invention is not limited to these examples, and it is needless to say that the present invention can be embodied in various forms without departing from the gist of the present invention. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0080] Example 1 (1st step) An ethyl cellulose-based binder resin was added to butyl acetate as a solvent to prepare a binder resin solution at a concentration of 5% by mass. For 60 parts by mass of the binder resin solution, the particle diameter in the number-based particle size distribution was D 10 Value 1.4μm, D 50 Value 2.5μm, D 90 A paste composition was prepared by adding 100 parts by mass of aluminum powder (JIS A1080) having a diameter of 4.0 μm and kneading. The obtained paste composition was applied to both sides of an aluminum foil having a thickness of 30 μm (aluminum 99.99% by weight) using a comma direct coater to adhere to both sides of the aluminum foil to a thickness of 50 μm, forming a coating. The composition was then dried at 100° C. for 1.5 minutes to obtain an unsintered laminate. The particle size in the particle size distribution based on the number of particles of the aluminum powder before sintering was measured by number-based particle size distribution measurement using a Microtrac MT3300EXII (manufactured by Nikkiso Co., Ltd.) by laser diffraction / scattering wet measurement, and the particle size was calculated as follows: D 10 Value, D 50 Value and D 90 The value was calculated. The particle diameter D of the powder in the sintered body based on the number of particles was 10 , D 50 , D 90 is the particle diameter D of the powder before sintering based on the number of particles 50 Since the particle diameter D of the aluminum powder before sintering hardly changes and is almost the same, 10 , D 50 , D 90 The measured value is the particle diameter D of the aluminum powder in the sintered body based on the number of particles. 10 , D 50, D 90 It was decided.
[0081] (2nd process) The unsintered laminate obtained in the first step was heated in an argon gas atmosphere at 615°C for 5 hours to sinter the composition, and a sintered body was formed on an aluminum foil substrate to produce an electrode material. When the thickness of the sintered body after sintering was measured, there was no change from the thickness of the paste composition of the unsintered laminate before sintering.
[0082] In the cross section of the sintered body, the maximum diameter (longest diameter) of each powder in the bonded state was taken as the particle diameter of that powder, and the particle diameter and number of all particles in a certain area in the cross section image were calculated. All the particles thus calculated were arranged in order of smallest particle diameter, and the particle diameter of the particle that accounts for 50% of the total number of particles was determined as the number-based particle diameter D of the powder in the sintered body. 50 The particle sizes that make up 10% and 90% of the total number of particles are defined as the particle sizes D based on the number of powder particles in the sintered body as shown below. 10 , D 90 The particle diameter D of the powder measured by the above measurement method was 50 is the particle diameter of the powder before sintering D 50 There was almost no change and it was almost the same.
[0083] The surface of the sintered body was photographed by a scanning electron microscope, and the images were processed by image analysis software, and then analyzed to count the number of powder particles with a particle size of 1 μm or less in an arbitrary region of 100 μm × 115 μm on the surface of the sintered body. The images of the surface of the sintered body photographed by a scanning electron microscope and processed by image analysis software are shown in Figs. 3 to 6. Fig. 3 is an image of Example 1, Fig. 4 is an image of Example 2, Fig. 5 is an image of Comparative Example 1, and Fig. 6 is an image of Comparative Example 5.
[0084] (Third step) The produced electrode material was further subjected to anodizing treatment at a formation voltage of 250 to 800 V in accordance with the Japan Electronics Industries Association standard RC-2364A.
[0085] (Examples 2 to 5, Comparative Examples 1 to 7) An electrode material was produced in the same manner as in Example 1, except that the powder was changed to one shown in Table 1 and the thickness of the sintered body was changed to one shown in Table 1, and an anodizing treatment was performed.
[0086] [Table 1]
[0087] For reference, the volumetric particle sizes of the powders A-1 and C used are shown in Table 2.
[0088] [Table 2]
[0089] (Capacitance evaluation test) In accordance with the Japan Electronics Industries Association standard RC-2364A, a capacitance evaluation test was carried out when the electrode materials of each of the examples and comparative examples were used.
[0090] (Bending strength evaluation test) The bending strength of the electrode material after the chemical conversion treatment was measured according to the MIT type automatic bending test method (Japan Electronics Industry Association standard RC-2364A) specified by the Japan Electronics Industry Association. The MIT type automatic bending tester used was a device specified by JIS P8115, and the number of bendings was the number of bendings at which each electrode material broke, and as shown in FIG. 7, it was counted as bending 90° once, returning to the original state twice, bending 90° in the opposite direction three times, and returning to the original state four times, and from the fifth time onwards, the bending operation was repeated in the same manner as the first to fourth times until the electrode material broke. The "Bending strength" column in Table 3 shows the number of folding operations (number of foldings) repeated until the electrode material broke after performing the above operation.
[0091] The results are shown in Table 3.
[0092] [Table 3]
[0093] From the results in Table 3, it was confirmed that the electrode material of each Example can exhibit the capacitance required for a capacitor and has excellent bending strength, compared to the electrode material of the corresponding Comparative Example.
[0094] Figure 1 shows the particle size distribution based on the number of particles of the powders used in Example 1 and Comparative Example 5. Figure 1 shows that the particle size distribution of the powder used in Example 1 has almost no peak in the small particle size region (2 μm or less), indicating that there are few particles with small particle sizes. In contrast, the particle size distribution of the powder used in Comparative Example 5 has a large peak at 0.81 μm, indicating that there are many particles with small particle sizes.
[0095] Figures 8 to 10 show images of the surface of the sintered electrode material produced according to Comparative Example 1 after a bending strength evaluation test was performed, taken with a SEM (scanning electron microscope). Figures 8 to 10 show images of the locations where cracks occurred. It was found from Figures 8 to 10 that fine powder aggregated to form secondary particles, and that these secondary particles were the starting points of the cracks. It is also thought from Figure 8 that the secondary particles affect the branching points of the cracks.
[0096] 11 and 12 show SEM images of the surface of the sintered body of the electrode material produced in Example 1. From Fig. 11 and Fig. 12, it can be seen that there is little fine powder in the sintered body.
[0097] Figures 13 and 14 show SEM images of the surface of the sintered compact of the electrode material produced in Comparative Example 1. Figures 15 and 16 show SEM images of the surface of the sintered compact of the electrode material produced in Comparative Example 4. Figures 13 to 16 show that a large amount of fine powder is observed in the sintered compact.
[0098] FIG. 17 shows an image taken with a SEM (scanning electron microscope) of the surface of the sintered electrode material produced according to Example 1 and after being folded twice in a folding strength evaluation test, i.e., after being folded once and then returned to its original state.
[0099] FIG. 18 shows an image taken with a SEM (scanning electron microscope) of the surface of the sintered electrode material produced according to Comparative Example 1 and after being folded twice in a folding strength evaluation test.
[0100] FIG. 19 shows an image taken with a SEM (scanning electron microscope) of the surface of the sintered electrode material produced in Comparative Example 5 and after being folded twice in a folding strength evaluation test.
[0101] 17, 18 and 19, it was found that not only was there a difference in the number of folds required to break, but also in the occurrence of cracks after one fold, and that when comparing the Examples and Comparative Examples with the same laminate thickness, the Examples had superior fold strength to the Comparative Examples.
Claims
1. An electrode material for an aluminum electrolytic capacitor having an aluminum foil substrate or an aluminum alloy foil substrate, on at least one surface of which is a sintered body of at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder, (1) the total thickness of the sintered body is 50 to 900 μm; (2) 10% particle diameter D in the number-based particle size distribution of the powder in the sintered body 10 is 1.0 to 1.8 μm, (3) 50% particle diameter D in the number-based particle size distribution of the powder in the sintered body 50 is 2.0 to 3.5 μm, (4) 90% particle diameter D in the number-based particle size distribution of the powder in the sintered body 90 is 3.8 to 6.0 μm; Electrode material for aluminum electrolytic capacitors.
2. 2. The electrode material for an aluminum electrolytic capacitor according to claim 1, wherein the number of powder particles having a particle diameter of 1 μm or less within any given region of 100 μm×115 μm on the surface of the sintered body is 300 or less.
3. 3. The electrode material for an aluminum electrolytic capacitor according to claim 1, further comprising an anodized film on a surface of the sintered body.
4. (1) A first step of forming a coating of a paste composition containing at least one type of powder selected from the group consisting of aluminum powder and aluminum alloy powder on at least one surface of an aluminum foil substrate or an aluminum alloy foil substrate; and (2) a second step of sintering the coating at a temperature of 560° C. or more and 660° C. or less; The powder has a 10% particle diameter D 10 is 1.0 to 1.8 μm, and the 50% particle diameter D 50 is 2.0 to 3.5 μm, and the 90% particle diameter D 90 is 3.8 to 6.0 μm; 2. The method for producing an electrode material for an aluminum electrolytic capacitor, comprising the steps of:
5. The method according to claim 4 , further comprising an anodizing treatment step after the second step.
Citation Information
Patent Citations
High capacitance capacitor anode
EP1818956A2
Electrode material for aluminum electrolytic capacitor, and its manufacturing method
JP2008098279A
Positive electrode active material for nonaqueous electrolyte battery, positive electrode for nonaqueous electrolyte battery, and nonaqueous electrolyte battery, and battery pack, electronic device, electric vehicle, power storage device, and electric power system comprising nonaqueous electrolyte battery
JP2012221855A
Electrode foil for aluminum electrolytic capacitor and production method for same
WO2015098644A1
Electrode material for aluminum electrolytic capacitors and method for producing same
WO2016136804A1